Stirring-assisted hydrothermal synthesis of ultralong α-MnO2 nanowires for oxygen reduction reaction. Issue 7 (27th April 2016) - Lei, Kaixiang; Cong, Liang; Fu, Xiaorui; Cheng, Fangyi; Chen, Jun
Abstract : Ultralong α-MnO2 synthesized by a stirring-assisted hydrothermal treatment of bulk MnO2 efficiently catalyzes the quasi-4-electron oxygen reduction reaction. Abstract : Ultralong MnO2 nanowires were synthesized through a facile hydrothermal treatment of bulk MnO2 along with magnetic stirring. Compared with commercial MnO2 powders, the synthesized nanowires exhibited higher catalytic activity and stability toward the oxygen reduction reaction.